Total Syntheses of (–)-7-epi-Alexine and (+)-Alexine Using Stereoselective Allylation - Myeong, In-Soo; Jung, Changyoung; Ham, Won-Hun (Synthesis, 2019)
Total syntheses of (–)-7-epi-alexine and (+)-alexine were achieved by using stereoselective allylation via a functionalized pyrrolidine obtained from an extended chiral 1,3-oxazine. The synthetic strategies include pyrrolidine formation via oxazine cleavage and diastereoselective allylations of a pyrrolidine aldehyde. (–)-7-epi-Alexine and (+)-alexine were synthesized from anti,syn,anti-oxazine in 12 steps.
Keywords: allylation; alkaloids; amino alcohols; diastereoselectivity; asymmetric synthesis; cyclization